Effect of different scaling instruments on the roughness of esthetic resin composite restorations: an in vitro study - Abdulkareem Alhumaidan; Turki Alshehri; Shahad T. Alameer; Dhai Albishri; Abdullah Al Madani; Mohammed Al Qranei; Hoda Albaqawi; Abdulrahman A. Balhaddad (Frontiers in Dental Medicine, 2026)
Objectives This in vitro study aimed to evaluate the effect of different scaling methods on the roughness of various resin composites used in anterior teeth. Methods Seven commercially available resin composite materials were tested: 3M™ Filtek™ Z350 XT, Beautifil II, and Beautifil II LS, G-ænial Anterior, IPS Empress Direct, Tokuyama PALFIQUE LX5, Vittra APS FKG. Disc-shaped specimens (6 mm in diameter and 2 mm in thickness) were prepared using a 3D-printed mold. A total of 30 specimens per brand were fabricated and randomly divided into three sub-groups according to the scaling technique: stainless-steel hand scaler (metal scaling), plastic hand scaler (plastic scaling), and piezoelectric ultra-sonic scaler tip (ultra-sonic scaling). Baseline surface roughness values were measured using a non-contact optical profilometer. Each specimen was then subjected to 40 scaling strokes, and post-scaling surface roughness was remeasured using the same method. The change in average surface roughness was calculated. Two and One-way ANOVA with Tukey's post hoc test analyzed the data ( α = 0.05). Results Both scaler method and resin composite type were determinant factors ( p < 0.001) in modulating the roughness of resin composite restorations. Metal scaling consistently produced the greatest surface roughness change ( Δ Ra, µm) across all composites, with G-ænial Anterior recording the highest Δ Ra value (2.23 ± 0.91 µm) and IPS Empress Direct the lowest (1.23 ± 0.82 µm). Plastic scaling resulted in the least Δ Ra across all materials (range: 0.00–0.10 µm), with IPS Empress Direct recording the highest change (0.10 ± 0.08 µm) and G-ænial Anterior and Tokuyama PALFIQUE LX5 revealing almost no change. Ultra-sonic scaling produced intermediate roughness change, with G-ænial Anterior again recording the highest value (1.61 ± 0.98 µm). Metal scaling produced significantly higher Δ Ra than both plastic and ultra-sonic methods in most resin composites ( p < 0.05), while plastic and ultra-sonic groups were largely comparable. Conclusion Within the limitations of the study, plastic scalers caused the least surface alteration and may be considered the most conservative option for maintaining the surface smoothness of resin composites.